The effect of a 3-sectioned movable spelling-vocabulary board on the indigenous people students’ English proficiency - Judith, Vanessa Joy Z. (Edelweiss Applied Science and Technology, 2025)
Improving the English proficiency of Indigenous People (IP) students in the Philippine hinterlands, a marginalized sector, poses a challenge for educators. Bereft of the amenities of the lowlands, the researcher designed a three-section movable vocabulary-spelling board to enhance the IP students' level of proficiency. The researcher adopted a single-group quasi-experimental design in conducting the pre-test and post-test using 20 vocabulary and spelling words taken from the Philippine Informal Reading Inventory (Phil-IRI) assessment tool. The researcher allotted a seven-week interval between the spelling and vocabulary pre-test and post-test. Mean and standard deviation, Wilcoxon signed-rank test, and t-test were used to analyze the data. Findings revealed that the respondents' English spelling and vocabulary skills in the post-tests were both high after the intervention, with a notable difference between the pre-tests and post-tests. The study highlights the positive effect of the instructional board and recommends further study of its usefulness in other disciplines.